Structural features and antioxidant activities of polysaccharides from different parts of Codonopsis pilosula var. modesta (Nannf.) L. T. Shen - Li-Xia Li; Li-Xia Li; Meng-Si Chen; Zi-Yu Zhang; Berit Smestad Paulsen; Frode Rise; Chao Huang; Bin Feng; Xing-Fu Chen; Ren-Yong Jia; Chun-Bang Ding; Shi-Ling Feng; et al. (Frontiers Media S.A., 2022)
In this study, three acidic polysaccharides from different plant parts of Codonopsis pilosula var. Modesta (Nannf.) L. T. Shen were obtained by ion exchange chromatography and gel filtration chromatography, and the yields of these three polysaccharides were different. According to the preliminary experimental results, the antioxidant activities of the polysaccharides from rhizomes and fibrous roots (CLFP-1) were poor, and was thus not studied further. Due to this the structural features of polysaccharides from roots (CLRP-1) and aerial parts (CLSP-1) were the object for this study and were structurally characterized, and their antioxidant activities were evaluated. As revealed by the results, the molecular weight of CLRP-1and CLSP-1 were 15.9 kDa and 26.4 kDa, respectively. The monosaccharide composition of CLRP-1 was Ara, Rha, Fuc, Xyl, Man, Gal, GlcA, GalA in a ratio of 3.8: 8.4: 1.0: 0.8: 2.4: 7.4: 7.5: 2.0: 66.7, and Ara, Rha, Gal, GalA in a ratio of 5.8: 8.9: 8.0: 77.0 in for CLSP-1. The results of structural elucidation indicated that both CLRP-1 and CLSP-1 were pectic polysaccharides, mainly composed of 1, 4-linked galacturonic acid with long homogalacturonan regions. Arabinogalactan type I and arabinogalactan type II were presented as side chains. The antioxidant assay in IPEC-J2 cells showed that both CLRP-1 and CLSP-1 promoted cell viability and antioxidant activity, which significantly increase the level of total antioxidant capacity and the activity of superoxide dismutase, catalase, and decrease the content of malondialdehyde. Moreover, CLRP-1 and CLSP-1 also showed powerful antioxidant abilities in Caenorhabditis elegans and might regulate the nuclear localization of DAF-16 transcription factor, induced antioxidant enzymes activities, and further reduced reactive oxygen species and malondialdehyde contents to increase the antioxidant ability of Caenorhabditis elegans. Thus, these finding suggest that CLRP-1 and CLSP-1 could be used as potential antioxidants.